Editorial - Fernández-Arata, Manuel (2022)
It is a pleasure to introduce volume 28, issue 2 (July - December) of Liberabit, Peruvian Journal of Psychology, which is made up of seven research articles described below. First, we present the work of María Gabriela Ramírez Jiménez, Norma Ivonne González-Arratia López-Fuentes, Ana Olivia Ruíz Martínez, Hans Oudhof van Barneveld and Blanca Estela Barcelata Eguiarte on religious coping and spirituality as mediators between perceived stress and resilience in adults with type 2 diabetes mellitus. They report that the lower the level of perceived stress, the higher the indexes of spirituality, religious coping, and resilience, as well as the effect of religious coping as a mediator between perceived stress and resilience.